The effectiveness of collaborative learning on civic education problem-solving abilities based on cognitive styles - S. Sucipto; Windi Setiawan; Ahmad Hatip (Universitas Muhammadiyah Malang, 2024)
Problem-solving ability is one of the competencies that individuals must have as a provision to face increasingly complex problems. This study aims to determine the effect of the application of the Collaborative Learning (CL) model on the problem-solving ability of civic education based on the cognitive style of students. This study applies the quantitative research paradigm with a quasi-experimental design. The research subjects were 162 students selected by cluster random sampling technique from two private universities in Surabaya, Indonesia. Data collection techniques use Cognitive Style Inventory (CoSI) and Problem Solving Inventory (PSI). The data were analyzed using an independent sample t test technique with SPSS software. The results showed that the application of the CL model had a significant effect on the problem-solving ability of civic education in students. The field independent (FI) cognitive style shows higher problem-solving ability than the field dependent (FD) in both the application of the CL model and the Cooperative Learning (CpL) model. In the learning process, it is recommended that educators apply the CL model as an alternative in improving the problem-solving ability of civic education by paying attention to the cognitive style of students.